Towards a comprehensive care system in Latin America. Legislative processes in capital cities and at the national level in Argentina and Mexico (2018-2020) - Vinokur, Mora (2025)
In this article we address the issue of care rights in Latin America, specifically in Argentina and Mexico, focusing in particular on the legislative processes related to comprehensive care systems at the sub-national and national levels. We draw on the cases of Mexico City (2018-2019) and the Autonomous City of Buenos Aires (2019) as well as the national level in each country, where there are ongoing legislative initiatives (2020). We take a comparative socio-historical and gender approach to show the social and political dynamics involved in the legislative processes that lead to the recognition of the rights of caregivers and the cared for in each case, at the subnational levels of the capital cities and the national level of both countries. Our categories of analysis are: the social conditions of gender violence; the social and political actors that participate in the construction of demand for comprehensive care legislation; and the political-cultural and formal-normative components of the legislative proposals presented. We identify differences between cases that we think contribute to unravelling the complexity of the legislative processes related to care rights in Latin America.